Akses Pelayanan Pengobatan Tuberkulosis Pada Masa Pandemi Covid-19 Di Puskesmas Abadijaya Kota Depok Tahun 2021 - Theresa F Napitupulu; Sabarinah Prasetyo (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
Health services at primary health care (puskesmas) is one of many public areas affected Covid-19. Being as determinants emergency health problem, the Government decided to implement the PSBB. Large-scale social restrictions affect regulation in health facilities in service delivery. Access to treatment such as TB treatment is often hampered. This study aims to evaluate access to tuberculosis treatment services at (Abadijaya Community Health Centre) during the Covid-19 pandemic. Study use explanatory research with mixed methods, conducted online survey on 21 respondents in the work area of ​​Puskesmas Abadijaya using google form to describe the frequency distribution of service access with 5A aspects (availability, affordability, acceptability, accessibility and accommodation). The qualitative approach was carried out on three informants, namely the head of the health center, the implementing doctor and the person in charge of the TB program through indepth interviews as source triangulation and document review. Based on the result  of research, the distribution of description TB respondents on five aspects of access to health services state that only two aspects meet the needs of respondents, that is the affordability (52.3%) and availability (57.1%), while the other three aspects are not easily accessible such as acceptability (33.3%) accessibility ( 33.3%), and accommodation (38%). These results were strengthened through in-depth interviews with puskesmas Abadijaya informants who stated that the puskesmas attempted to facilitate TB treatment using telemedicine, appropriate drug distribution and there were no restrictions on TB treatment in health services during the Covid-19 period so that it could be accessed and reached by TB sufferers. However, there is still a gap between the perceptions of health workers and TB sufferers who felt that services were not acceptable during the Covid period, as well as lack of accessibility and difficult to reach accommodation